Spectroscopic characterization and life time study of Manganese doped and undoped zinc sulfide nanocrystals. - Thuan, Dao Nguyen. (2009)
Doping ZnS nanocrystals with Mn2+ ions allows it to emit in the orange region and opens up its applications in electroluminescent displays, spintronics and biomedical labeling. One of the most interesting aspects of ZnS:Mn nanoparticles is the elucidation of factors that influence the shortening of their luminescence lifetime, which is important for their applications as phosphor and sensor materials. While several researchers have investigated this, it is not well understood. The motivation for this research, is to perform a systematic study in order to gain a fundamental understanding of the factors influence the luminescence of ZnS and ZnS:Mn nanocrystals. The successful doping of Mn was confirmed by various spectroscopic characterization techniques. Theoretical calculation for particle sizes was suitable with HR-TEM images and PLE spectra, which showed the effect of quantum confinement in synthesized nanocrystals.